GHMP gene family: identification, evolutionary and expression analysis under various exogenous hormones and abiotic stress in tomato - Haitao Yang; Xin Bai; Tayeb Muhammad; Tao Yang; Chunping Jia; Baike Wang; Qinghui Yu; Juan Wang (BMC Plant Biology)
Abstract Background The GHMP kinase gene family is a class of structurally similar protein kinases that have been named by combining the first letter of its four members, galactokinase (GALK), homoserine kinase (HSK), mevalonate kinase (MK) and phosphomevalonate kinase (PMK). It plays a pivotal role in regulating plant growth and development, as well as mediating various responses. However, the identification and functional analysis of GHMP family members in tomato have not been carried out yet. Results This study presents a comprehensive analysis of the GHMP gene family in cultivated tomato and three wild tomato species. The analysis encompasses phylogenetic classification, gene structure, collinearity, physical and chemical features, cis-acting elements, tissue-specific expression, and hormonal and abiotic stress responses. A total of 56 GHMP genes were identified in the four tomato species. The phylogenetic analysis classified the GHMP members into 10 subfamilies, which is in agreement with the results of motif distribution and gene structure analysis. Members of the same subfamily tend to exhibit similar or identical motif types and order of distribution. The synteny analysis suggests that dispersed and single-copy replication may have played a role in the expansion of the GHMP gene family in tomatoes with pure selection. A diverse set of cis-acting elements was identified in the promoters of the GHMPs, includingelements related to growth and development, hormone and stress responses and transcription factor interaction binding sites, indicating a multifaceted role of the GHMPs in tomato. RNA-seq data analysis revealed that GHMP members exhibited differential expression in distinct tissues, signifying their involvement in tomato growth and development. In response to exogenous hormonal and abiotic treatments, FKGP, PMK1, ARA1, PMK2, GALAK2 and ISPE were upregulated by hormonal treatments, while ISPE, PMK1, ARA1, ARA2, and MK responded to abiotic stresses. Conclusions Overall, the findings of this study contribute to a deeper understanding of the GHMP gene family, which could serve as a foundation for future investigations of their biological function, particularly in response to hormonal and abiotic stress.